Paul and His Recent Interpreters - Wright, N. T. (Nicholas Thomas) (Book collections on Project MUSE., 2015)
This companion volume to N. T,. Wright's Paul and the Faithfulness of God and Pauline Perspectives is essential reading for all with a serious interest in Paul, the interpretation of his letters, his appropriation by subsequent thinkers, and his continuing significance today. In the course of this masterly survey, Wright asks searching questions of the major contributors to Pauline studies in the last fifty years. From back cover.